THE INFLUENCE OF THE PRINCIPAL'S LEADERSHIP STYLE AND INTRINSIC MOTIVATION ON TEACHER PERFORMANCE WITH JOB SATISFACTION AS INTERVENING IN PUBLIC ELEMENTARY SCHOOLS IN CILEGON CITY - Reni Andryani; Sutisna Sutisna; Mamay Komarudin (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
The success of quality education depends on optimizing efforts to improve the professionalism of educators, which is called optimizing teacher performance. Teacher performance is one of the main factors that determine the success of the education process in schools, this is because the performance of a teacher will affect students' interest in learning which has an impact on student achievement and a decrease in the quality of education quality in schools. This study aims to analyze the effect of the relationship between teacher performance and the principal's leadership style, intrinsic motivation, and job satisfaction. The method used in this research is path analysis method with quantitative approach and using SmartPLS 4.0 for data processing. The results state that the principal's leadership style, intrinsic motivation, and job satisfaction affect teacher performance by 85.7%, meaning that as much as 85.7% of teacher performance is influenced by the three variables above and only 14.3% is influenced by other variables outside the study. In addition, leadership style and intrinsic motivation also affect job satisfaction by 52.7% and only 47.3% is influenced by variables outside this study. Based on the results of the study, it is concluded that the variables of principal leadership style, intrinsic motivation and job satisfaction have a positive and significant effect on teacher performance. Then the principal's leadership style and intrinsic motivation also have a positive and significant effect on job satisfaction.